The Use of Liquid Rubber Smoke as PGR on Coffee Seeds Germination - Hajar Setyaji; Suryanto; Mukhsin (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objectives of this research is to obtain the best concentration of liquid rubber smoke as a growth regulator in the germination of Arabica, Robusta and Liberica coffee seeds. Method of research: location of the research was on Seed Technology Laboratory University of Jambi, the research design was carried out using a randomized block design consisting of a factorial pattern based on 3 factors (Types of Coffee species: Arabica from Kerinci, Robusta from Merangin, and Liberica from Tanjung Jabung Barat), 3 levels of treatment for providing liquid smoke rubber 0%, 2.5%, 5%, by soaking for 5 minutes. With 3 repetitions test. Statistical data analysis by anova using SPSS. The result shows that 3 species of coffee give different response of the treatments, Arabica and Robusta seeds species has relative equal statistical response to Liberica coffee, concentration 2.5% of diluted liquid rubber smoke give the best germination and vigor seeds response performance.